BRCA1 and BRCA2 Mutations in Ethnic Lebanese Arab Women With High Hereditary Risk Breast Cancer. (16th March 2015) - El Saghir, Nagi S.; Zgheib, Nathalie K.; Assi, Hussein A.; Khoury, Katia E.; Bidet, Yannick; Jaber, Sara M.; Charara, Raghid N.; Farhat, Rania A.; Kreidieh, Firas Y.; Decousus, Stephanie; Romero, Pierre; Nemer, Georges M.; et al.
Abstract: Purpose: Breast cancer is the most common malignancy among women in Lebanon and in Arab countries, with 50% of cases presenting before the age of 50 years. Methods: Between 2009 and 2012, 250 Lebanese women with breast cancer who were considered to be at high risk of carrying BRCA1 or BRCA2 mutations because of presentation at young age and/or positive family history (FH) of breast or ovarian cancer were recruited. Clinical data were analyzed statistically. Coding exons and intron-exon boundaries of BRCA1 and BRCA2 were sequenced from peripheral blood DNA. All patients were tested for BRCA1 rearrangements using multiplex ligation-dependent probe amplification (MLPA). BRCA2 MLPA was done in selected cases. Results: Overall, 14 of 250 patients (5.6%) carried a deleterious BRCA mutation (7 BRCA1, 7 BRCA2 ) and 31 (12.4%) carried a variant of uncertain significance. Eight of 74 patients (10.8%) aged ≤40 years with positive FH and only 1 of 74 patients (1.4%) aged ≤40 years without FH had a mutated BRCA . Four of 75 patients (5.3%) aged 41–50 years with FH had a deleterious mutation. Only 1 of 27 patients aged >50 years at diagnosis had a BRCA mutation. All seven patients with BRCA1 mutations had grade 3 infiltrating ductal carcinoma and triple-negative breast cancer. Nine BRCA1 and 17 BRCA2 common haplotypes were observed. Conclusion: Prevalence of deleterious BRCA mutations is lower than expected and does not support the hypothesis that BRCA mutations alone cause the observed high percentage of breast cancer in young women of Lebanese and Arab descent. Studies to search for other genetic mutations are recommended. Abstract : The aim of this study was to determine the prevalence and role of BRCA1 and BRCA2 mutations in Lebanese women with breast cancer who were at high risk of harboring hereditary disease. The prevalence of deleterious BRCA mutations was lower than expected and does not support the hypothesis that BRCA mutations alone cause the observed high percentage of breast cancer in young women of Lebanese and Arab descent.